Functional Characterization and Toxicological Study of Proanthocyanidins in Weaned Pigs - Jiahao Liu; Yong Qiao; Bing Yu; Yuheng Luo; Zhiqing Huang; Xiangbing Mao; Jie Yu; Ping Zheng; Hui Yan; Yan Li; Jun He (Toxins, 2023)
Proanthocyanidin (PRO) has been implicated in a variety of biological functions, such as antibacterial, antioxidant, and anti-obesity effects. However, little is known about its safety dose for animals. To explore its safety and effect on growth performance and intestinal health, thirty weaned pigs were divided into five groups and fed with basal diet containing 0, 30, 300, 600, and 1200 mg/kg PRO for 42 days. Results showed that PRO supplementation at 30 and 300 mg/kg significantly decreased the feed/gain ratio (F:G) and diarrhea rate (p < 0.05). PRO also increased the digestibilities of dry matter, ether extract, gross energy, and ash (p < 0.05). Interestingly, PRO not only elevated the villus height and the ratio of villus height to crypt depth (V/C) in duodenum and jejunum (p < 0.01), but also decreased the crypt depth in the duodenum (p < 0.01). Moreover, PRO supplementation at 30, 300, and 600 mg/kg elevated the expression levels of mucin 1 (MUC1), MUC2, and fatty acid transport protein 1 (FATP-1) in the duodenum (p < 0.05). The expression levels of FATP-4 in jejunum and ileum were also elevated by PRO (p < 0.05). Importantly, histopathological findings of tissues (e.g., heart, liver, kidney, spleen, lungs, pancreas, thymus, mesenteric lymph nodes, stomach, small intestine), serum clinical chemistry, and major hematological parameters were not affected by PRO supplementation. These results suggest that PRO may act as a safe and effective supplement to decrease F:G and improve intestinal health in weaned pigs.